The Culture of Stigma Surrounding Depression in the African American Family and Community - Wimberley, Wynnetta (2015)
This article explores the crisis of depression in post-modern America through the contextualized lens of the African American experience. In view of the pervasive societal realities of race, class, and gender oppression, the article begins by identifying the American trans-Atlantic slave trade as an historical trauma and cultural factor for depression among (enslaved and freed) Africans and persons of African descent. It highlights the cultural stigmatization of depression as a prevailing challenge facing African Americans today. The author concludes the article by drawing from a communal-contextual model of Black pastoral theology to offer both the Black pastor and the 'extended family' network of the African American congregation as vital resources in countering the effects of the cultural stigmatization of depression.
Keywords: Collective Memory; counseling African Americans; cultural stigmatization; Depression; Historical trauma; societal oppression; Stress